Analisis Kemampuan Pemecahan Masalah Mahasiswa Pada Mata Kuliah Persamaan Differensial - Novitasari, Pratiwi; Siti Aisyah, Amiratih (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This research is a qualitative study which aims to describe students' problem solving abilities in solving problems related to differential equations. Differential equation questions are limited to material regarding separate and homogeneous differential equations. The subjects in this research were 5th semester students of the Mathematics Education Study Program. The instruments used in this research were differential equation questions and interview guidelines. The results of the research show that high category students are able to understand the problem well, which is indicated by students being able to explain well what is meant in the problem. Students are able to plan solutions well, are less able to carry out planning, and based on the results of the interview, the student rechecks the final answer. Low category students are less able to understand the problem well, which is indicated by the student's inability to explain what is meant in the problem. Students are unable to plan solutions. Students do not carry out solution planning, which is characterized by the student's inability to solve the problems given. Based on the results of the interview, students did not carry out the stage of rechecking the final answer.